2014
DOI: 10.1590/0047-2085000000003
|View full text |Cite
|
Sign up to set email alerts
|

Atendimento a tentativas de suicídio por serviço de atenção pré-hospitalar

Abstract: rESUMo objetivo: Investigar as características das vítimas de tentativa de suicídio atendidas em serviço pré-hospitalar e os intervalos de tempo consumidos nessa fase de atendimento. Méto-dos: Estudo transversal utilizando dados da fase pré-hospitalar de atendimento às vítimas de tentativa de suicídio no município de Arapiraca, no ano de 2011. Para análise dos dados, foram realizados teste exato de Fisher, teste t de Student e regressão logística múltipla. resultados: Foram atendidas 80 vítimas de tentativa de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1
40

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 17 publications
0
16
1
40
Order By: Relevance
“…10 Other studies have reported more cases of suicide attempts among women, corroborating our findings. [11][12][13][14][15] Women attempt suicide more often than men, but men use more lethal methods. 3,13 In some studies, a lower occurrence of suicide among women has been attributed to a low prevalence of alcohol dependence, greater religiosity, social involvement, and influence of the roles of mother, wife, and daughter.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other studies have reported more cases of suicide attempts among women, corroborating our findings. [11][12][13][14][15] Women attempt suicide more often than men, but men use more lethal methods. 3,13 In some studies, a lower occurrence of suicide among women has been attributed to a low prevalence of alcohol dependence, greater religiosity, social involvement, and influence of the roles of mother, wife, and daughter.…”
Section: Discussionmentioning
confidence: 99%
“…This method is the most chosen because it is less invasive and, consequently, does not affect aesthetics. In the present study, 41.9% of the reported cases were due to poisoning/ intoxication, mainly due to ingestion of alcohol, and medication 12,13 .…”
Section: Discussionmentioning
confidence: 46%
“…Men commit more suicides and prefer methods that evidence their virility, using lethal means such as hanging, firearm and precipitation of high places 13 . Table 1 showed that self-injury and suicide attempt occurred mainly among elderly men, with ages between 60 and 69 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses elementos podem ser representados, respectivamente, por meio dos pensamentos de autodestruição, da autoagressão, manifestada por gestos suicidas e por tentativas de suicídio e, finalmente, da consumação do suicídio (Werlang, Borges & Fensterseifer, 2005). Diversos estudos correlacionam a ideação suicida com o maior risco de tentativas de suicídio e com o ato consumado (Suominen et al, 2004;Vidal, Gontijo & Lima, 2013), mostrando que, de fato, a presença de ideação e, principalmente, de uma história de tentativas de suicídio têm sido consideradas como importantes preditores na avaliação frente ao risco de suicídio (Magalhães et al, 2014;Soares, 2003). Nesse sentido, é possível estimar que a associação e a frequência elevada desses fatores ampliam significativamente esse risco.…”
unclassified